Follicular fluid steroid and gonadotropic hormone levels and mitochondrial function from exosomes predict embryonic development - Yu, Li; Liu, Miao; Xu, Shiji; Wang, Zhenxin; Liu, Te; Zhou, Jiaye; Zhang, Doudou; Dong, Xi; Pan, Baishen; Wang, Beili; Liu, Suying; Guo, Wei (Frontiers in Endocrinology, 2022)
Abstract: Purpose Human follicular fluid (FF) is a complex biological fluid that contributes to the microenvironment of oocyte development. The aim of this study was to evaluate the role of steroid and gonadotropic hormones levels and mitochonrial function in embryo development during in vitro fertilization cycles. Methods This was a cohort study of 138 women receiving IVF/ICSI, including 136 FF samples from 109 infertile women. FF steroid and gonadotropic hormones levels were tested by liquid chromatography-tandem mass spectrometry (LC-MS/MS) and immunoassays. The mRNA expression levels of mitochondrial electron transport chain (ETC) complex genes from FF exosomes were detected by qPCR. Results Analysis of these individual FF concentrations revealed that LH and FSH concentrations were higher in follicles in which the oocyte developed into a top quality (TQ) blastocyst (LH: 9.44±2.32mIU/ml, FSH: 9.32±1.01mIU/ml) than those in which there was a failure of fertilization (LH: 5.30±0.84mIU/ml, FSH: 6.91±0.62mIU/ml). In contrast, follicular cortisone concentrations were the lower for oocytes that resulted in a TQ blastocyst (12.20±0.82mIU/ml). The receiver operating characteristic analysis showed that FF LH and FSH levels predicted TQ blastocyst with excellent AUC value of 0.711 and 0.747. Mitochondrial ETC complex I and III mRNA levels were increased in the FF exosomes of TQ blastocyst. Correlation analysis showed that mRNA levels of ETC complex I was positively correlated with LH and FSH levels in FF. Conclusion The levels of FF steroid and gonadotropic hormones from single follicle can predetermine subsequent embryo development to some extent. Furthermore, impaired exosome mitochondrial dysfunction is a potiential event that causes hormone change in embryo development.